Inovasi Dan Perubahan Dalam Pendidikan Islam - Apriliansyah Apriliansyah; Qolbi Khoiri (Journal on Education, 2023)
This paper discusses Innovation and Change in Islamic Education. This research method uses literature research or library research to be analyzed and concluded. In collecting data, the author uses literature study, namely research conducted by using data related to Innovation and Change in Islamic Education from books, journals, the internet and other relevant sources. The results of this study are that innovation in Islamic religious education is an act that should not be carried out, the causative factors can be observed very complex, both from policy changes, developments in science and technology and the condition of an increasingly mature society in following various information media about Islamic education religious materials.